2004
DOI: 10.1007/s00213-003-1672-y
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the response to chronic l-dopa in patients with schizophrenia: therapeutic and heuristic implications

Abstract: . In patients already on antipsychotic drugs, the addition of L-dopa can be beneficial. Dopamine agonists merit further consideration as adjuncts to antipsychotic drugs in the treatment of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 77 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…The increased availability of dopamine in the prefrontal cortex may not only contribute to improve the effect on cognitive symptoms, but can probably also, in the presence of a D 2 antagonist, contribute to enhance the antipsychotic effect per se. Previous clinical studies show that low doses of L-dopa used as adjunct treatment to conventional APDs may enhance their therapeutic effect in schizophrenic patients (see Jaskiw and Popli, 2004), and experimental data reveal that adding low doses of L-dopa to raclopride not only caused a preferentially increased prefrontal cortical dopamine output, but also potentiated the antipsychotic-like effect of the D 2/3 antagonist (Eltayb et al, 2005). Therefore, addition of drugs that are able to increase the availability of cortical monoamines, for example, reboxetine and idazoxan, to APDs may both enhance the antipsychotic effect, as well as improve negative or depressive symptoms and certain aspects of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The increased availability of dopamine in the prefrontal cortex may not only contribute to improve the effect on cognitive symptoms, but can probably also, in the presence of a D 2 antagonist, contribute to enhance the antipsychotic effect per se. Previous clinical studies show that low doses of L-dopa used as adjunct treatment to conventional APDs may enhance their therapeutic effect in schizophrenic patients (see Jaskiw and Popli, 2004), and experimental data reveal that adding low doses of L-dopa to raclopride not only caused a preferentially increased prefrontal cortical dopamine output, but also potentiated the antipsychotic-like effect of the D 2/3 antagonist (Eltayb et al, 2005). Therefore, addition of drugs that are able to increase the availability of cortical monoamines, for example, reboxetine and idazoxan, to APDs may both enhance the antipsychotic effect, as well as improve negative or depressive symptoms and certain aspects of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that add-on levodopa may be beneficial in patients already on antipsychotics [93]. It is noteworthy that the beneficial effects of levodopa prevailed over its negative effects even though high doses of levodopa, associated with a peripheral decarboxylase inhibitor, were given.…”
Section: Overcoming the Metabolic And Cardiovascular Side Effects Of mentioning
confidence: 99%
“…In these studies no exacerbation of psychotic symptoms was reported. Levodopa has also been used as add-on in 5 placebo-controlled studies in patients with schizophrenia and a meta-analysis of these studies found a beneficial overall effect (because of the variety of outcome measures used in these studies, patients were divided in two response groups on the basis of their response in the scale used in the individual studies for the purposes of the meta-analysis: poor response = no change or worsening and good response = improved) with a medium-large ES (Cohen's d= 0.71) and no worsening of any symptoms of schizophrenia (Jaskiw and Popli, 2004). There was however clinical worsening in 38% of the patients who received high doses of levodopa without concomitant antipsychotics.…”
Section: Which Cognitive-enhancing Drugs?mentioning
confidence: 99%